2012
DOI: 10.1097/tp.0b013e31825668f6
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Severe Hepatitis C Virus Recurrence After Liver Transplantation in Patients With a T Allele of IL28B rs12979860

Abstract: The recipient IL28B rs12979860 genotype has a major influence on the posttransplantation course of HCV infection, being a valuable biomarker for patient care in liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Although recipient rs12979860 CC genotype confers higher rates of spontaneous and treatment-related HCV clearance in the non-transplant setting, here, we found that receiving a donor liver with the rs12979860 CC genotype is associated with increased risk of severe recurrent HCV after LT. This finding is supportive of two recent smaller studies where donor rs12979860 CC was associated with unfavorable post-LT events (higher risk for recurrent cirrhosis, need for retransplantation or death) and donor rs12979860 T allele with favorable post-LT events (lower risk for advanced fibrosis within 5 years)[21, 22]. Similarly, for rs8099917 (for which in the non-transplant setting the TT genotype is favorable) in our study the TT donor was associated with increased rather than reduced risk of severe HCV after LT.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although recipient rs12979860 CC genotype confers higher rates of spontaneous and treatment-related HCV clearance in the non-transplant setting, here, we found that receiving a donor liver with the rs12979860 CC genotype is associated with increased risk of severe recurrent HCV after LT. This finding is supportive of two recent smaller studies where donor rs12979860 CC was associated with unfavorable post-LT events (higher risk for recurrent cirrhosis, need for retransplantation or death) and donor rs12979860 T allele with favorable post-LT events (lower risk for advanced fibrosis within 5 years)[21, 22]. Similarly, for rs8099917 (for which in the non-transplant setting the TT genotype is favorable) in our study the TT donor was associated with increased rather than reduced risk of severe HCV after LT.…”
Section: Discussionsupporting
confidence: 85%
“…The relevance of IL28B polymorphisms (rs12979860 or rs8099917) to the severity of HCV recurrence and outcome after LT has been only incompletely characterized in five small single-center studies that included both donor and recipient DNA analysis[17-21]. In the largest of these studies an unfavorable genotype (rs12979860 TT) in the recipient was associated with more aggressive recurrent HCV, whereas a favorable genotype (rs12979860 CC) in the donor or recipient was associated with higher response rates to HCV treatment[17].…”
Section: Introductionmentioning
confidence: 99%
“…Eurich et al found no association with rs8099917 post-LT fibrosis progression, yet observed higher inflammation and higher ALT levels with the G allele (27). For rs1297860, several studies have now found the T allele to be associated with more rapid fibrosis progression (25, 28, 29). However, Lange et al found no association with post-LT viremia or aminotransferase levels and this recipient genotype (26).…”
Section: Discussionmentioning
confidence: 99%
“…Other gene regions have also been implicated in fibrosis progression, including the DEAD box protein 5 (DDX5) (19, 20), PNPLA3 (2123), and suppressor of cytokine signaling-3 (SOC-3) (24). However, only limited studies have focused on contribution of host genetics to fibrosis progression in HCV-related LT. Studies focusing on the IL28B region and HCV-related LT have produced conflicting results (2529). These studies have used different IL28B SNVs, often focusing only one SNV, and have used different phenotypes, which makes comparison of results difficult.…”
mentioning
confidence: 99%
“…It was reported that any genetic variants that affect OAS1 activity could be important determinants of susceptibility/resistance to antiviral treatment and to virus-related disease progression [14]. Recently it was demonstrated that IL-28 β SNPs play important roles in the management of hepatitis C virus (HCV) infections and are strongly associated with spontaneous and treatment-induced HCV clearance [11, 15, 16]. …”
Section: Introductionmentioning
confidence: 99%